2022
DOI: 10.1038/s41467-022-33964-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TFPI as a receptor reveals recombination-driven receptor switching in Clostridioides difficile toxin B variants

Abstract: Toxin B (TcdB) is a major exotoxin responsible for diseases associated with Clostridioides difficile infection. Its sequence variations among clinical isolates may contribute to the difficulty in developing effective therapeutics. Here, we investigate receptor-binding specificity of major TcdB subtypes (TcdB1 to TcdB12). We find that representative members of subtypes 2, 4, 7, 10, 11, and 12 do not recognize the established host receptor, frizzled proteins (FZDs). Using a genome-wide CRISPR-Cas9-mediated scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 82 publications
(157 reference statements)
1
13
0
Order By: Relevance
“…Subsequently, the cells are exposed to toxins as a phenotypic selection, usually through multiple rounds, to minimize contaminants. The surviving cells at the end of the selection can be expanded and analyzed using advanced sequencing techniques to determine the specific genes involved (Figure 2) [31][32][33][34][35]. The RNAi screen is easy to handle and can be applied to multiple cell lines to achieve high genome coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the cells are exposed to toxins as a phenotypic selection, usually through multiple rounds, to minimize contaminants. The surviving cells at the end of the selection can be expanded and analyzed using advanced sequencing techniques to determine the specific genes involved (Figure 2) [31][32][33][34][35]. The RNAi screen is easy to handle and can be applied to multiple cell lines to achieve high genome coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TcdB variants have been shown to use different receptors to gain entry into mammalian host cells, including the CSPG4, Frizzled, and TFPI protein receptors. 20,21 Given that multiple TcdA and TcdB variants have been identified, it is essential to evaluate TcdA and TcdB-targeted therapeutics for the inhibition of multiple variants.…”
mentioning
confidence: 99%
“…Two recent studies have proposed grouping TcdB toxin variants into either 8 or 12 subtypes (TcdB1-B12). , Compared to TcdB, TcdA showed far fewer variations in both studies. , Sequence variations in the toxin genes could influence receptor binding, specificity toward Rho GTPases, antigenicity, and overall toxicity. Furthermore, TcdB variants have been shown to use different receptors to gain entry into mammalian host cells, including the CSPG4, Frizzled, and TFPI protein receptors. , Given that multiple TcdA and TcdB variants have been identified, it is essential to evaluate TcdA and TcdB-targeted therapeutics for the inhibition of multiple variants.…”
mentioning
confidence: 99%
“…It was shown that the CROPs domain of TcdA was capable of binding the trisaccharide Gal-α1,3-Gal-β1,4-GlcNAc and thus considered as a domain responsible for binding carbohydrate moieties on cell surface 36,37 . In recent years, multiple protein receptors for LCTs were identified, including low-density lipoprotein receptor-related protein 1 (LRP1) for TpeL 38 , low-density lipoprotein receptor (LDLR) family proteins for TcdA and Tcnα [39][40][41][42] , chondroitin sulfate proteoglycan 4 (CSPG4), poliovirus receptorlike 3 (PVRL3), Frizzled proteins (FZDs), and tissue factor pathway inhibitor (TFPI) for TcdB 33,[43][44][45][46] , Semaphorin 6 A and 6B (SEMA6A/6B) for TcsL 47,48 , and transmembrane serine protease 2 (TMPRSS2) for TcsH 49 . Many of them were structurally validated to bind LCTs independent of the CROPs 33,48,50,51 , raising the speculation that the CROPs in LCTs are not solely for host recognition but have uncharacterized functions.…”
mentioning
confidence: 99%